Nanoliposome-loaded antifungal drugs for dermal administration: A review - Peyman Asadi; Ahmad Mehravaran; Nahid Soltanloo; Mahdi Abastabar; Javad Akhtari (Mazandaran University of Medical Sciences, 2021)
Cutaneous fungal infections are the fourth most common health problem, which involves approximately  billion people worldwide. Drug delivery to the skin seems to be the best choice for superficial fungal infections. Topical formulations can release a sufficient amount of drug in therapeutical concentrations and permeate higher layers of the skin like the stratum corneum. As the outermost layer of the epidermis, the stratum corneum prevents the drug from penetrating the skin. Liposomes, especially nanosized as topical drug delivery systems to the skin, can show various functions depending on their size, lipids and cholesterol components, the percent of ingredients, lamellarity, and surface charge. Nanoliposomes can increase permeation through the stratum corneum, decrease systemic effects with their localizing actions, and overcome many dermal drug delivery obstacles. Antifungal drugs, such as croconazole, econazole, fluconazole, ketoconazole, terbinafine hydrochloride, tolnaftate, and miconazole entrapped in liposomes have indicated improved skin penetration and localizing effects. According to the literature review summarized in this paper, many studies have identified liposomes as a powerful carrier for topical antifungal drug delivery to the skin. However, a few studies introduced new generations of liposomes like ethosomes and transfersomes. This paper was conducted on almost all liposomal studies of antifungal drugs with dermal application.